2012
DOI: 10.1103/physrevd.85.083528
|View full text |Cite
|
Sign up to set email alerts
|

Light propagation and the average expansion rate in near-FRW universes

Abstract: We consider universes that are close to Friedmann-Robertson-Walker in the sense that metric perturbations, their time derivatives and first spatial derivatives are small, but second spatial derivatives are not constrained. We show that if we in addition assume that the observer four-velocity is close to its background value and close to the four-velocity which defines the hypersurface of averaging, the redshift and the average expansion rate remain close to the FRW case. However, this is not true for the angul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 125 publications
(248 reference statements)
7
37
0
Order By: Relevance
“…This was expected from theoretical considerations, see e.g. [53,54], but we quantify this statement numerically.…”
Section: Discussionmentioning
confidence: 75%
“…This was expected from theoretical considerations, see e.g. [53,54], but we quantify this statement numerically.…”
Section: Discussionmentioning
confidence: 75%
“…It is supposed to represent the 4−velocity field of the observers. In the application paper [75], this field is restricted to be everywhere very close to n (and so has a small vorticity), whereas n is assumed to be chosen such that it builds hypersurfaces of statistical homogeneity and isotropy. These restrictions are already both suggested in the original paper [74] but the equations are kept general.…”
Section: Smirnov [82]mentioning
confidence: 99%
“…We emphasize that this interpretation tacitly considers the averaged expansion rate as the relevant physical quantity to describe the dynamics of the Universe, which is a highly non-trivial, and widely debated assumption. Notable contributions to this debate [55,[73][74][75] concluded that, in a fluid-filled and shell-crossing-free universe, the spatially averaged expansion rate really governs the angular distance-redshift relation, and therefore has a powerful physical and observational meaning. However, there is a priori not reason why this result should hold for a more realistic description of the Universe, with shell crossings, formation of virialised structures decoupled from the expansion, etc.…”
Section: Backreaction and Swiss-cheese Modelsmentioning
confidence: 99%